Ferromagnetism in Co-doped ZnO films grown by molecular beam epitaxy: magnetic, electrical and microstructural studies - Strelchuk, V.V.; Bryksa, V.P.; Avramenko, K.A.; Lytvyn, P.M.; Valakh, M.Ya.; Pashchenko, V.O.; Bludov, O.M.; Deparis, C.; Morhain, C.; Tronc, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
We studied structural, optical and magnetic properties of high-quality 5 and 15% Co-doped ZnO films grown by plasma-assisted molecular beam epitaxy (MBE) on (0001)- sapphire substrates. Magnetic force microscopy (MFM) and magnetic measurements with a SQUID magnetometer show clear ferromagnetic behavior of the films up to room temperature, while they are antiferromagnetic below approximately 200 K. Temperature dependences of the carrier mobility were determined using Raman line shape analysis of the longitudinal optical phonon-plasmon coupled modes. It has been show that the microscopic mechanism for ferromagnetic ordering is coupling mediated by free electron spins of Co atoms. These results bring insight into a subtle interplay between charge carriers and magnetism in MBE-grown Zn₁₋xCoxO films.